In pursuit of votes: The capture of the allocation of local public goods by the central state in Ghana - Horowitz, Leah; Palaniswamy, Nethra (International Food Policy Research Institute, 2010)
Decentralization reforms have been the overwhelming response to failures in the targeting of public resources by the central state in developing countries. The policy debate on decentralization typically revolves around several a priori hypotheses on how the design of formal institutions of local government, such as electoral rules, affects accountability in the provision and targeting of public goods. Yet a growing body of research suggests that many rules that structure political incentives and policy outcomes are informal. Indeed, it is widely acknowledged that informal rules such as legislative norms and clientelism can strongly influence political behavior and policy outcomes. This evidence makes a compelling case for both the impact of these informal institutions on political incentives and their role in complementing formal institutions and shaping the status quo when formal venues are absent or weak. How much do these formal institutions matter? How do they shape policy outcomes? In particular, do they merely substitute for weak or absent formal institutions or do they exist alongside and dominate these formal rules and institutions? In this paper, we examine the effect of informal institutions on decentralized public-resource allocation in Ghana. The decentralization policy debate in Ghana, as elsewhere, typically focuses on the role of formal institutions of local government in the targeting of local public resources. Through a comparative case study of two districts in northern Ghana, we argue that informal institutions, grounded in the rationale of partisan politics of the central state, are the key determinants of decentralized public-resource allocation outcomes. In particular, we show that this political rationale is expressed through an informal model of vote buying, and this vote buying is dictated by a national political agenda. Our findings suggest that ignoring this informal institution is likely to undermine the current efforts to reform decentralized public-resource allocation in Ghana.